DEFAMILIARISING SUFISM IN THE ISLAMIC-MALAY TRADITION OF POETRY: A TEXTUAL AND HISTORICAL ANALYSIS ON SYAIR BURUNG PUNGGUK THROUGH ISLAMIC REGIONAL STUDIES - Dian Nurrachman; Asep Achmad Hidayat (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2025)
Syair Burung Pungguk is one of the classical Malay poems depicting the spiritual and existential struggle of humanity through the symbolism of longing and solitude. Through the lens of Islamic World Area Studies, this text can be read as a representation of the transformation of Islamic values rooted in the local experiences of the Malay society in Southeast Asia. This study applies a hermeneutic-cultural approach with the principle of defamiliarization to reinterpret the poem within the Islamic cultural context of the region. The analysis was conducted on the translated version Syair Burung Pungguk by Arief Rahman and Didik Purwanto (2021, National Library Press) by considering the textual side through the concept of defamiliarization combined with the perspective of Islamic Regional Studies. The findings suggest that the symbolism of the owl and the moon reflects the unique Malay-Islamic religiosity centered on mystical longing for the Divine, reaffirming that literature serves as an arena where universal Islamic teachings are aesthetically and culturally localized. Thus, this poem is not merely a literary artifact but a site of encounter between the universal principles of Islam and the cultural expressions of the Malay world rooted in Sufi sensibility.